Problem Behaviors among Israeli undergraduate students: Applying Jessor's Problem Behavior Theory (PBT) among young adult students - Liat eKorn; Yael eShaked; Haya eFogel-Grinvald (Frontiers Media S.A., 2014)
Purpose: The current study tested the applicability of Jessor's problem behavior theory (PBT) in a large academic institution in Israel. Methods: A structured, self-reported, anonymous questionnaire was administered to undergraduate students. The final study sample included 1,360 participants (882 females and 478 males, mean age 25, SD=2.9, Range=23).Results: Findings indicated that the PBT was replicated in this sample. As shown from the hierarchal linear regression model, religiosity and high academic achievements were found to be strong and significant protective factors that reduce risk behaviors. Among young and religious students, the personal vulnerability has almost no impact on involvement in risk behaviors.Conclusions: The PBT finds empirical support in this young adult undergraduate Israeli sample.